Unlocking fluency: evaluating the Japanese language mastery program - Zubbir, Nadiah; Abas, Noor Aizah; Hashim, Haida Umiera (Universiti Teknologi MARA, 2025)
The Japanese language and culture were first introduced into Malaysian education through the Dasar Pandang ke Timur (DPT) (literally “Look East Policy), initiated by Tun Dr. Mahathir Mohamad in 1982, aiming to emulate successful East Asian practices for Malaysia's development, particularly Japan and South Korea. Initially, Japanese was taught primarily at higher education institutions and selected secondary schools, but not at the elementary level. The Japanese Language Mastery Program (JLMP) at Universiti Teknologi MARA (UiTM) Shah Alam was introduced in two foster schools in the Klang Valley as part of the university’s commitment to University Social Responsibility (USR), addressing this educational gap. This study evaluates the program's effectiveness in improving students' Japanese proficiency and cultural understanding. Using pre- and post-surveys conducted via Google Forms, involving 61 respondents, the study assessed participants' satisfaction, knowledge, skills, and attitudes towards Japanese. The findings revealed a significant increase in students' interest in Japanese, notable improvements in language skills, and a deepened appreciation for cultural diversity. The JLMP not only enhanced language proficiency but also broadened students' cultural awareness, fostering a greater appreciation of Japanese culture. This initiative not only fills educational gaps but also fosters collaboration between higher education and schools. Future programs should consider longer class durations, explore various foreign languages, and conduct longitudinal studies to assess the long-term benefits of early language and cultural exposure.